Indian head massage - Airey, Muriel Burnham (Thomson Learning, 2005)
Indian Head Massage: A Practical Guide, Second Edition has been extensively revised to provide comprehensive coverage for all Indian head massage courses, including BTEC and VTCT awards. Published by Thomson Learning in association with Habia, this exciting new edition provides a complete guide for students wishing to gain a professional qualification in Indian head massage, whatever their mode of learning - college, work-based, part-time or evening courses, or self-study. All aspects of Indian head massage, from massage technique to anatomy and physiology, are covered using an interactive workbook approach. This practical textbook offers a total learning package, complete with clear step-by-step instructions and photographic sequences to take the reader through each skill